Strain measurement based on fixed wavelength transmission of tapered long-period fiber grating - Tang, Young; Zhang, Hao; Zhang, Li; Yu, Xin Feng; Bai, Yun Feng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
This paper studies the relationship between transmission intensity and strain based on tapered long-period fiber grating at a fixed wavelength. In experiments, tapered long-period fiber grating was prepared by the electric melting method. Experimental results show that two resonance peaks appeared at 1482 and 1537 nm, respectively. Here is the elaboration of the relationship between the resonant wavelength and the strain, its wavelength-strain sensitivity is 20 pm/με, and the linearity was negative. Then our next study was about the relationship between transmission intensity and strain at a fixed wavelength. The results show that the transmission intensity at a fixed wavelength is related to the exponent with strain. The coupled-mode theory is applied to simulate the relationship between fixed wavelength and strain. The simulation results matched the experimental results. Two fixed wavelength transmission intensity ratio was used, and the ratio showed a linear relationship with the strain, and the slope is –0.018 dB/με. Therefore, within the 0.01% resolution of our detector, we could resolve a 0.16 με strain change. We can select the appropriate light source and detector to achieve higher measurement accuracy. Thus, there is a great potential in fiber grating strain sensors.
Optica Applicata, Vol. 52, 2022, nr 4, s. 511-519
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; tapered long-period fiber grating; strain sensors; fixed dual-wavelength ratio